Overlapping authorities, vikings in Frisia and the church of Utrecht. - McNair, Fraser (Historical Research, 2024)
In 858 King Lothar II granted Bishop Hunger of Utrecht the abbey of Sint Odiliënberg to serve as a refuge against viking attacks. This article examines the political circumstance surrounding this event, arguing that the Utrecht clergy's relocation was not a straightforward response to viking violence but was instead the result of pressures upon them caused by Frisia's place at the centre of difference circles of overlapping authority. Through taking Frisia's role in multiple polities and sub-polities seriously, I offer a new interpretation of the events of 858 and point to some further implications for earlier medieval politics.